Percutaneous dilatational tracheostomy: A prospective analysis among ICU patients - Khawaja Kamal Nasir, Khawaja Kamal Nasir; Faraz Mansoor , Faraz Mansoor; Shahzad Hussain Waqar, Shahzad Hussain Waqar; Shahab Zahid Ahmed Khan, Shahab Zahid Ahmed Khan; Rakhshanda Jabeen, Rakhshanda Jabeen (Journal of Rawalpindi Medical College, 2020)
Introduction: Percutaneous dilatational tracheostomy (PDT) is a simple bedside procedure, particularly useful in the intensive care units. Over the last few decades, the technique of PDT has gained popularity due to its comparable safety to the more surgical tracheostomy (ST). Objective: To describe the outcome of PDT using modified Ciaglia’s technique in patients of Surgical ICU. Methodology: This was a prospective cohort study that analysed the outcomes of PDTs carried out on critically ill patients admitted in the surgical ICU, Pakistan Institute of Medical Sciences, Islamabad from August 2015 to January 2017. All PDTs were performed by the presiding consultant and his team using modified Ciaglia’s (Blue Rhino) technique. The main outcome was the frequency of perioperative and early complications within the first six days. Demographic variables and complications were recorded. Data was analysed using SPSS version 18. Results: Seventy-four patients underwent PDTs in the surgical ICU with mean age of the patients was 49.17 ± 12.82 years. The commonest indication of tracheostomy was prolonged mechanical ventilation followed by failure to wean. Complications rate was 12.16% of which perioperative bleeding occurred in 6.7% of patients. Early complications within the first six days were wound infection, tube displacement and blocked tube. Conclusion: PDT is a valuable, efficacious and safe method that can be performed at the bedside with minimal complication rate and needs to be considered more frequently in the intensive care units in developing countries.